2003
DOI: 10.1073/pnas.0300372101
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of transactivation from transrepression by a selective glucocorticoid receptor agonist leads to separation of therapeutic effects from side effects

Abstract: Glucocorticoids (GCs) are the most commonly used antiinflammatory and immunosuppressive drugs. Their outstanding therapeutic effects, however, are often accompanied by severe and sometimes irreversible side effects. For this reason, one goal of research in the GC field is the development of new drugs, which show a reduced side-effect profile while maintaining the antiinflammatory and immunosuppressive properties of classical GCs. GCs affect gene expression by both transactivation and transrepression mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
309
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(318 citation statements)
references
References 31 publications
2
309
0
7
Order By: Relevance
“…This finding was further demonstrated by its lack of activity in a rat model of hot flush or preventing ovariectomy-induced bone loss (data not shown). This approach has also been accomplished with the glucocorticoid receptor in which two nonsteroidal ligands have been identified that are more selective for transrepression than transactivation (42,43). We believe WAY-169916 will provide a similar antiinflammatory activity without the side effects associated with either glucocorticoid or estrogen therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was further demonstrated by its lack of activity in a rat model of hot flush or preventing ovariectomy-induced bone loss (data not shown). This approach has also been accomplished with the glucocorticoid receptor in which two nonsteroidal ligands have been identified that are more selective for transrepression than transactivation (42,43). We believe WAY-169916 will provide a similar antiinflammatory activity without the side effects associated with either glucocorticoid or estrogen therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This insight initiated a new wave of pharmacological research directed toward the development of so-called dissociated ligands, favoring only GR-mediated transrepression of NF-B-or AP-1-driven gene expression (35)(36)(37)(38). Surprisingly, not all steroidal ligands that had dissociated properties in vitro also displayed these characteristics in vivo, especially with regard to the side-effect profile (35).…”
Section: Discussionmentioning
confidence: 99%
“…These dissociated steroids, including RU24858 and RU40066, have antiinflammatory effects in vitro [106], although there is little separation of anti-inflammatory effects and systemic sideeffects in vivo [107]. Other dissociated corticosteroids appear to show dissociation in vivo [108]. Several dissociated corticosteroids are now in clinical development and may lead to inhaled steroids with greater safety, or even to oral steroids which are less likely to produce significant adverse effects.…”
Section: Dissociated Corticosteroidsmentioning
confidence: 99%